2017
DOI: 10.1124/mol.116.107102
|View full text |Cite
|
Sign up to set email alerts
|

p38βMitogen-Activated Protein Kinase Signaling Mediates Exenatide-Stimulated Microglialβ-Endorphin Expression

Abstract: Recent discoveries established that activation of glucagon-like peptide-1 receptors (GLP-1Rs) mediates neuroprotection and antinociception through microglial -endorphin expression. This study aimed to explore the underlying signaling mechanisms of microglial-endorphin. GLP-1Rs and -endorphin were coexpressed in primary cultures of microglia. Treatment with the GLP-1R agonist exenatide concentration-dependently stimulated microglial expression of the-endorphin precursor gene proopiomelanocortin (POMC) and pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 76 publications
2
26
0
1
Order By: Relevance
“…It was reported that selective p38 activation inhibitor SB203580 cannot reverse neuropathic pain when given to animals after neuropathy was established72. Our recent study reported that knockdown of spinal p38α or p38β expression was not antiallodynic62. Our current results demonstrated that multiple-daily injections of siRNA/p38α or siRNA/p38β did not alter mechanical thresholds in the ipsilateral paws in neuropathic rats.…”
Section: Discussionsupporting
confidence: 47%
“…It was reported that selective p38 activation inhibitor SB203580 cannot reverse neuropathic pain when given to animals after neuropathy was established72. Our recent study reported that knockdown of spinal p38α or p38β expression was not antiallodynic62. Our current results demonstrated that multiple-daily injections of siRNA/p38α or siRNA/p38β did not alter mechanical thresholds in the ipsilateral paws in neuropathic rats.…”
Section: Discussionsupporting
confidence: 47%
“…Most of the published work so far refers to p38α and only few data is available distinguishing both isoforms, mainly because the main p38 inhibitors target both isoforms [32]. However, a recent report showed that siRNA-mediated downregulation of p38β, but not of p38α, resulted in impaired Creb1 activation in microglia [33]. These results are in good concordance with our results showing that p38α (Mapk14, Additional file 3) did not come up as positive hit in our primary screen for deactivating-microglia drug targets.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, treatment with cynandione A (100 µM) stimulated the mRNA expression of IL-10 and POMC in cultured primary microglial cells. Pretreatment (30 minute earlier) with H-89 (10 µM [50]) completely hindered cynandione A-stimulated but not baseline expression of IL-10 or POMC (p < 0.05, by one-way ANOVA followed by the post-hoc Student-Newman-Keuls test; Fig. 9D, 9E).…”
Section: Cynandione a Stimulated Il-10 And β-Endorphin Expression In mentioning
confidence: 92%
“…In addition, four groups of neuropathic rats (n = 6 per group) received intrathecal injection of saline (10 µL) or the speci c PKA activation inhibitor H-89 (5 µg, dosage of which was based on the previous study [50]) 30 minutes before intrathecal injection of the vehicle (10 µL) or cynandione A (100 µg). As shown in Fig.…”
Section: Cynandione a Stimulated Il-10 And β-Endorphin Expression In mentioning
confidence: 99%